Through the looking glass and what Alice found there - Carroll, Lewis, 1832-1898.; Tenniel, John, Sir, 1820-1914 (New York : Puffin Books, 2003)
In this sequel to "Alice in Wonderland," Alice goes through the mirror to find a strange world where curious adventures await her.
First published in 1872.
7.6
5-8
Keywords: Alice (Fictitious character : Carroll) -- Juvenile fiction; Alice (Fictitious character : Carroll) -- Fiction; Fantasy; Alice (Fictional character : Carroll) -- Fiction; Fantastic fiction; Fantastic fiction